2018
DOI: 10.1007/s10865-018-9934-7
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal depression prevention through home visitation: a cluster randomized trial of mothers and babies 1-on-1

Abstract: Postpartum depression is highly prevalent in low-income women and has significant health effects on mother and child. This pilot study tested the effectiveness of the newly adapted Mothers and Babies (MB) 1-on-1 intervention. A cluster randomized trial was conducted with 8 programs using trained home visitors to deliver MB 1-on-1 and 6 delivering usual home visiting. One hundred twenty pregnant women not experiencing major depression were enrolled. Outcomes were assessed at baseline and 3- and 6-months postpar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 50 publications
0
48
0
7
Order By: Relevance
“…Third, we observed that a high proportion (60%) of participants in the control group showed remission at 6 months which also accounted for waning intervention effects at 6 months compared with 3 months, as observed in other perinatal depression trials. 29,30 The most likely explanation for this remission is the natural history of the condition, in particular for mild and moderate cases. 31 In addition it may be plausible that some non-specific elements, for example the participation in the research interviews or the enhancement of usual care, may have mediated symptom improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we observed that a high proportion (60%) of participants in the control group showed remission at 6 months which also accounted for waning intervention effects at 6 months compared with 3 months, as observed in other perinatal depression trials. 29,30 The most likely explanation for this remission is the natural history of the condition, in particular for mild and moderate cases. 31 In addition it may be plausible that some non-specific elements, for example the participation in the research interviews or the enhancement of usual care, may have mediated symptom improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Treatments involving education and early support for mothers were found to be helpful in addressing early symptoms as well as reducing the long-term detrimental effects of PPD (Brazeau et al, 2018). focuses on mood, stress and attachment of mother and infant (Tandon et al, 2018). IPT is a brief and present-focused therapy that centers on the interpersonal context of depression (Carter et al, 2010).…”
Section: Variety Of Approachesmentioning
confidence: 99%
“…The literature highlighted the success of interventions that focused on education and empowerment of mothers (Tandon et al, 2018;McFarlane et al, 2016;Thitipitchayanant et al, 2018;Turan et al, 2018). For the purpose of this study, empowerment is defined as the increasing self-efficacy, knowledge and competence that comes from working toward a self-determined goal (Cattaneo & Chapman, 2010).…”
Section: Focus On Empowermentmentioning
confidence: 99%
See 1 more Smart Citation
“…These interventions are often delivered by non-mental health professionals such as nurses and home visitors. 5,6 The evidence for the superiority of these interventions has been mixed, which has been partially attributable to the success of usual care provided by home-visiting programmes and the occasional high attrition rate in trials.…”
Section: Service Development Psychotherapy For Prevention and Treatmementioning
confidence: 99%